Dalbavancin as Secondary Therapy for Serious Staphylococcus aureus Infections in a Vulnerable Patient Population. (30th January 2019) - Bryson-Cahn, Chloe; Beieler, Alison M; Chan, Jeannie D; Harrington, Robert D; Dhanireddy, Shireesha
Abstract: We retrospectively evaluated off-label use of dalbavancin as secondary therapy in 32 patients with serious Staphylococcus aureus infections (endocarditis, osteomyelitis, septic thrombophlebitis, epidural infection) who were also persons who use drugs. The majority of patients (56%) had a clinical response to treatment. Only 1 patient who completed the intended dalbavancin course experienced a treatment failure.